Uang Kuliah Tunggal (UKT) for Students in 2018 - M. Yusuf Daeng; Ruslihardy (Jurnal Niara, 2020)
The background of this research is problems relates to implementation of the Uang Kuliah Tunggal Policy in the Faculty of Social and Political Sciences (FISIP) University of Riau. UKT is a policy of Single Tuition for students. The purpose of this study is to evaluate the implementation of the Single Tuition Policy (UKT) at the Faculty of Social and Political Sciences, University of Riau in 2018. The research method used is descriptive method with a qualitative approach. Informants were determined by purposive method. The technique of collecting data uses observation, interviews and documentation. The results of the study indicate that effectiveness, adequacy, responsiveness and accuracy in implementing the policy have been fulfilled. Whereas for efficiency and equity is not yet fully fulfilled